Crystallization and preliminary X-ray diffraction analysis of YisP protein from Bacillus subtilis subsp. subtilis strain 168 - Hu, Yumei (International Union of Crystallography, 2012)
YisP is an enzyme involved in the pathway of biofilm formation in bacteria and is predicted to possess squalene synthase activity. A BlastP search using the YisP protein sequence from Bacillus subtilis subsp. subtilis strain 168 shows that it shares 23% identity with the dehydrosqualene synthase from Staphylococcus aureus. The YisP from B. subtilis 168 was expressed in Escherichia coli and the recombinant protein was purified and crystallized. The crystals, which belong to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 43.966, b = 77.576, c = 91.378 Å, were obtained by the sitting-drop vapour-diffusion method and diffracted to 1.92 Å resolution. Structure determination using MAD and MIR methods is in progress.